2013
DOI: 10.1007/s12223-013-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in uterus of healthy and metritic postpartum Holstein dairy cows

Abstract: Clone library of bacterial 16S rRNA gene was constructed to evaluate the bacterial diversity and community structure of uterus samples obtained from three postpartum healthy cows and three metritic cows on days 10 and 40. Sequences were assigned to five major groups (Bacteroidetes, Firmicutes, Fusobacteria, Proteobacteria, and Tenericutes) and to an uncultured group. On day 10, Bacteroidetes, Firmicutes, and Fusobacteria were the dominant group both in healthy and metritic cows. On day 40, the major sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…In this study, Bacteroidetes was the only phylum with significantly higher abundance in metritic than in healthy cows, therefore indicating that Bacteroidetes may be an important phylum for the development of metritis in dairy cows. Two recent studies using clone library sequencing found either an overwhelming predominance of Fusobacteria in metritic cows (5) or an overall predominance of Bacteroidetes in both metritic and healthy cows (6). One study using pyrosequencing observed a predominance of Bacteroidetes and Fusobacteria in both metritic and healthy cows (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Bacteroidetes was the only phylum with significantly higher abundance in metritic than in healthy cows, therefore indicating that Bacteroidetes may be an important phylum for the development of metritis in dairy cows. Two recent studies using clone library sequencing found either an overwhelming predominance of Fusobacteria in metritic cows (5) or an overall predominance of Bacteroidetes in both metritic and healthy cows (6). One study using pyrosequencing observed a predominance of Bacteroidetes and Fusobacteria in both metritic and healthy cows (7).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cultureindependent techniques such as clone library sequencing (5,6) and pyrosequencing (7,8) have been used to characterize the uterine microbiota of cows with metritis (5-7) and endometritis (7,8). Sequencing using the Illumina platform allows for deeper sequencing than has previously been feasible even with pyrosequencing (9).…”
mentioning
confidence: 99%
“…Von Chamier et al (2012) reported that intra-uterine experimental infection in mice with U. parvum was able to induce sepsis with severe fetal infl ammatory response. Thus, the host immune response could be a determinant factor in the severity of disease, since immunosuppressed animals are more likely to develop a systemic response (Famuyide et al 2009, Peng et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vaccines containing components of E. coli, F. necrophorum and/or T. pyogenes protect animals against postpartum uterine disease (Nolte et al, 2001;Machado et al, 2014). However, metagenomics techniques have found associations between uterine disease and bacteria that are not readily cultured by standard techniques (Machado et al, 2012;Santos and Bicalho, 2012;Peng et al, 2013;Knudsen et al, 2015;Wagener et al, 2015). Whilst some of the studies find E. coli, T. pyogenes and the expected anaerobic bacteria, others report finding Bacteroidetes and Firmicutes.…”
Section: Microbes That Cause Uterine Diseasementioning
confidence: 99%